Analytical Modeling of Oil Production from a Matrix Block by Free Fall Gravity Drainage Mechanism. Issue 6 (December 2013) - Ghorbanizadeh, Salman; Ardakany, Muhammad Shojaadini; Ghazanfari, Mohammad Hossein
Free fall gravity drainage is the most effective mechanism in gas invaded zone of fractured reservoirs. Although several analytical models have been proposed to characterize this mechanism, most of them suffer from inadequate reality, such as neglecting capillary pressure. In this study, a new analytical model was proposed to predict the oil recovery versus time for a homogeneous matrix block under a free fall gravity drainage mechanism. Considering the effect of viscous, gravity as well as capillary forces, the model was developed. This model is applicable to different conditions of gravity and capillary force, as well as when both forces are active. Along with core scale experimental data available in the literature, a series of micro model experiments was also conducted and used to check the model's validity. In addition, a synthetic computer model was constructed and used for further model validation. Results showed that the suggested model predicts the physics of the gravity drainage mechanism very well. The results of this work can be helpful to develop a new transfer function for gravity drainage process modeling in fractured reservoir.